Catalyst composition, preparation method and application of catalyst composition in preparation of light aromatic hydrocarbon by biomass cracking
By using a catalyst composition of Fe modified dolomite particles and La modified molecular sieve, the problems of poor stability and carbon decompression in the preparation of light aromatic hydrocarbons in biomass cracking are solved, and the effect of efficient preparation of light aromatic hydrocarbons is achieved.
Patent Information
- Application Number
- CN202411830260.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-21
AI Technical Summary
The existing catalyst compositions have poor stability and carbon deposit inactivation in the preparation of light aromatic hydrocarbons in biomass cracking, resulting in unsatisfactory catalytic effect.
Fe modified dolomite particles and La modified molecular sieve are used as catalyst compositions to form the first catalyst and the second catalyst through mechanical mixing and sintering, respectively, to enhance the C-C bond cracking ability and catalytic bio-oil cracking ability of long-chain hydrocarbon compounds in bio-oils, and to improve the stability and resistance to carbon deposits of the catalyst.
It significantly improves the content of light aromatic hydrocarbons in bio-oils, extends the service life of the catalyst, improves the stability and carbon deposit resistance of the catalyst, and improves the effect of biomass cracking to prepare light aromatic hydrocarbons.
Smart Images

Figure CN119657203A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of biomass energy utilization, and specifically, to a catalyst composition, a preparation method, and its application in the preparation of light aromatics by biomass cracking. Background Art
[0002] As a non-renewable energy source, the continuous consumption of fossil fuels is gradually causing a serious crisis of energy depletion. Therefore, the development and utilization of renewable clean energy has received more and more attention. Biomass energy is an important energy source after coal, oil and natural gas, and it is also the only renewable energy that can be converted into a variety of energy products such as gas, liquid and solid. Due to its easy access, environmental friendliness, low cost and convenient transportation and processing, it has attracted widespread attention from the world. The liquid product (bio-oil) obtained by biomass conversion contains rich aromatic substances, among which light aromatics (BTX) play an important role in the petrochemical industry. It can be used as an additive, solvent or raw material for engine fuel for product synthesis, such as rubber, preservatives, plastics, fibers and resins.
[0003] However, although bio-oil has the advantages of easy processing and transportation, high energy density, and can be used as fuel and chemical raw materials, the bio-oil produced by ordinary pyrolysis has complex components, high viscosity, poor stability, and corrosiveness, which limit its direct application value. In addition, bio-oil contains a large amount of volatile organic compounds (VOC) and polycyclic aromatic hydrocarbons (PAH), which have a great negative impact on industrial production, daily life and the environment. At present, the more promising technologies for improving the yield of aromatics and BTX in bio-oil mainly include catalytic cracking of bio-oil, catalytic hydrogenation of bio-oil, and emulsification of bio-oil and diesel.
[0004] Among them, catalytic pyrolysis technology is the most studied conversion technology in the application research of bio-oil modification technology. The bio-oil obtained by adding appropriate catalysts to catalyze rapid pyrolysis can effectively increase the yield of light aromatics such as BTX and improve the quality of bio-oil. Therefore, designing catalysts with excellent performance is a research hotspot for the preparation of BTX by catalytic pyrolysis of biomass.
[0005] However, the current catalyst compositions, preparation methods, and applications thereof in the preparation of light aromatics by biomass cracking still need to be improved. Summary of the invention
[0006] The present application aims to provide a catalyst and a preparation method thereof to solve or alleviate one or more technical problems in the related art.
[0007] As mentioned above, molecular sieve catalysts are widely used in the preparation of light aromatics to upgrade bio-oil because of their bond-breaking and shape-selective catalytic abilities, as well as good deoxygenation and arylation abilities. Among them, the microporous ZSM-5 molecular sieve is the most commonly used catalyst for the preparation of aromatics by biomass pyrolysis. Because of its special pore structure and acidic environment, it has significant advantages in the preparation of high-quality chemicals by biomass pyrolysis. However, the molecular sieve has a small pore size and is prone to coking, which causes pore blockage and catalyst deactivation. Therefore, if a catalyst or catalyst composition can be provided that can achieve a stable increase in the content of light aromatics in the catalytic preparation of bio-oil, it will alleviate or even solve the above problems to a large extent.
[0008] In one aspect of the present application, the present application proposes a catalyst composition for preparing light aromatic hydrocarbons by cracking biomass. The catalyst composition comprises a first catalyst and a second catalyst, wherein the first catalyst comprises Fe-modified dolomite particles, and the second catalyst comprises La-modified molecular sieves, wherein the Fe-modified dolomite particles are formed by mechanically mixing and sintering an iron-containing raw material and the dolomite, and the Fe content in the Fe-modified dolomite particles is 4-8wt%; the La-modified molecular sieve is formed by sintering a molecular sieve impregnated with lanthanum nitrate, and the La content in the La-modified molecular sieve is 3-8wt%.
[0009] The catalyst composition can improve the CC bond cracking ability of long-chain hydrocarbon compounds through the first catalyst, obtain free radicals and promote the ring-opening reaction of aromatic hydrocarbons, thereby improving the conversion of macromolecular bio-oil into small molecular substances, thereby alleviating the problems of contact obstruction and carbon deposition deactivation of the active center of the molecular sieve. At the same time, the use of La-modified molecular sieve as the second catalyst can improve the catalytic bio-oil cracking ability, improve the cracking effect of the intermediate, improve the stability of the catalyst, and improve the catalyst's ability to resist carbon deposition. Therefore, the catalyst composition used for the preparation of light aromatic hydrocarbons by biomass cracking can have the advantages of a high content of light aromatic hydrocarbons in the product.
[0010] According to an embodiment of the present application, the specific surface area of the first catalyst is 15-30 m 2 / g, the evaluation pore size of the first catalyst is 20-30nm. This is conducive to further improving the catalytic effect.
[0011] According to an embodiment of the present application, the specific surface area of the second catalyst is 280-350 m 2 / g. This is beneficial to further enhance the catalytic effect.
[0012] In another aspect of the present application, the present application proposes a method for preparing the aforementioned catalyst composition, the method comprising: mixing and stirring an iron-containing raw material with dolomite, and performing a first calcination treatment on the mixed raw material to prepare a first catalyst; preparing an inorganic salt solution of La, and using the inorganic salt solution to impregnate a molecular sieve, and performing a second calcination treatment on the molecular sieve after the impregnation treatment to prepare a second catalyst. The method can easily obtain the aforementioned catalyst composition.
[0013] According to an embodiment of the present application, the iron-containing raw material includes limonite, the dolomite is pre-ground, screened and subjected to a third calcination treatment, the temperature of the third calcination treatment is 850-1000° C., and the time is 2-4 hours. The preparation of the first catalyst includes:
[0014] The limonite and the dolomite subjected to the third calcination treatment are mixed in a mass ratio of 0.5-1 and stirred evenly, pseudo-boehmite binder and water are added to prepare slurry, and granulation treatment is performed, the particles obtained by the granulation treatment are dried, and the first calcination treatment is performed, and the temperature of the first calcination treatment is 700-900°C and the time is 2-4h.
[0015] According to an embodiment of the present application, the molecular sieve is pre-screened and subjected to a fourth calcination treatment, the temperature of the fourth calcination treatment is 500-600° C., and the time is 3-6 hours. The preparation of the second catalyst includes:
[0016] A La(NO3)3·6H2O solution with a concentration of 0.05mol / L-0.13mol / L is prepared, and the treated molecular sieve is impregnated, wherein the impregnation treatment includes impregnation for 1.5-3h under stirring conditions, the molecular sieve that has undergone the impregnation treatment is dried and the dried solid is sieved to 100 mesh, a pseudo-boehmite binder and water are added to prepare a slurry, wherein the mass fraction of the pseudo-boehmite is 20-30wt%, and granulation treatment is performed, the particles obtained by the granulation treatment are dried, and the second calcination treatment is performed, wherein the temperature of the second calcination treatment is 500-600°C and the time is 3-6h.
[0017] In another aspect of the present application, the present application proposes a method for preparing light aromatics by cracking biomass using the above-mentioned catalyst composition, the method comprising:
[0018] After the two-stage tube furnace is heated to the preset temperature, an inert gas is introduced for gas replacement;
[0019] Adding biomass raw materials and a first catalyst into the first-stage tubular furnace, and adding a second catalyst into the second-stage tubular furnace to perform pyrolysis treatment;
[0020] The bio-oil produced by the pyrolysis treatment is collected by a condensing device, and the light aromatics are obtained by separation.
[0021] This method can effectively improve the content of light aromatics in the obtained bio-oil.
[0022] According to an embodiment of the present application, heating the two-stage tubular furnace to a preset temperature includes: heating the first stage tubular furnace to 800-900° C. at a heating rate of 15-25° C. / min, and heating the second stage tubular furnace to 450-850° C. The reforming treatment temperature of the pyrolysis treatment is 450-850° C.
[0023] According to an embodiment of the present application, during the pyrolysis treatment, the flow rate of the inert gas introduced is 50-250 mL / min.
[0024] According to an embodiment of the present application, the mass ratio of the first catalyst to the second catalyst is 1:2-2:1.
[0025] The bio-oil prepared under the above conditions has a higher content of light aromatics.
[0026] The above summary is for the purpose of description only and is not intended to be limiting in any way. In addition to the illustrative aspects, embodiments and features described above, further aspects, embodiments and features of the present application will be readily apparent through the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 A schematic diagram of an apparatus used in a method for preparing light aromatic hydrocarbons by cracking biomass according to an embodiment of the present application is shown;
[0028] Figure 2 The XRD spectrum of the first catalyst prepared in one embodiment of the present application is shown;
[0029] Figure 3-Figure 5 The SEM image of the first catalyst prepared in one embodiment of the present application is shown;
[0030] Figure 6 The EDS energy spectrum scanning diagram of the first catalyst prepared in one embodiment of the present application is shown;
[0031] Figure 7 The XRD spectrum of the second catalyst prepared in one embodiment of the present application is shown;
[0032] Figure 8 shows a SEM image of a second catalyst prepared in one embodiment of the present application;
[0033] Fig. 9shows a SEM image of a second catalyst prepared in one embodiment of the present application;
[0034] Fig.10 The energy spectrum scanning diagram of the second catalyst prepared in one embodiment of the present application is shown;
[0035] Fig.11 The relative peak area diagram of each component in the bio-oil prepared in some examples of the present application is shown;
[0036] Fig.12 The relative peak area diagram of each component in the bio-oil prepared in some examples of the present application is shown;
[0037] Fig.13 The relative peak area diagram of each component in the bio-oil prepared in some examples of the present application is shown;
[0038] Fig.14 The relative peak area diagram of each component in the bio-oil prepared in some examples of this application is shown. DETAILED DESCRIPTION
[0039] In the following, only some exemplary embodiments are briefly described. As those skilled in the art will appreciate, the described embodiments may be modified in various ways without departing from the spirit or scope of the present application, and different embodiments may be combined arbitrarily without conflict. Therefore, the following description is considered to be exemplary and non-restrictive in nature.
[0040] In one aspect of the present application, the present application proposes a catalyst composition for preparing light aromatic hydrocarbons by cracking biomass. The catalyst composition comprises a first catalyst and a second catalyst, wherein the first catalyst comprises Fe-modified dolomite particles, and the second catalyst comprises La-modified molecular sieves, wherein the Fe-modified dolomite particles are formed by mechanically mixing and sintering an iron-containing raw material and the dolomite, and the Fe content in the Fe-modified dolomite particles is 4-8wt%; the La-modified molecular sieve is formed by sintering a molecular sieve impregnated with lanthanum nitrate, and the La content in the La-modified molecular sieve is 3-8wt%.
[0041] The catalyst composition is used for the pyrolysis treatment of preparing light aromatic hydrocarbons by cracking biomass. First, the CC bond cracking ability of long-chain hydrocarbon compounds in bio-oil in biomass raw materials can be improved through the first catalyst, free radicals can be obtained and the ring-opening reaction of aromatic hydrocarbons can be promoted, thereby improving the conversion of macromolecular bio-oil into small molecular substances, thereby alleviating the problem of contact obstruction and carbon deposition deactivation of the active center of the molecular sieve when the subsequent second catalyst contacts the reactant. At the same time, the use of La-modified molecular sieve as the second catalyst can improve the catalytic bio-oil cracking ability, improve the cracking effect of the intermediate, improve the stability of the catalyst, and improve the catalyst's ability to resist carbon deposition. Therefore, the catalyst composition used for preparing light aromatic hydrocarbons by cracking biomass can have the advantages of a high content of light aromatic hydrocarbons in the product.
[0042] Specifically, the first catalyst is a dolomite catalyst modified with Fe (hereinafter referred to as Fe-Dol). After modification, the specific surface area of the first catalyst is significantly increased, and the anti-sintering and anti-carbon deposition capabilities are also improved. The modified first catalyst also promotes the reinforcement of the catalyst microporous structure, improves the oxygen carrying capacity of the catalyst, and can further strengthen the breaking of the carbon-carbon bonds at both ends of the long-chain hydrocarbons to form hydrogen free radicals, while promoting the ring-opening reaction of aromatic hydrocarbons, and converting the macromolecular bio-oil into small molecular substances.
[0043] According to the embodiment of the present application, the specific surface area of the first catalyst is 15-30m 2 / g, the evaluation pore size of the first catalyst is 20-30nm. This is conducive to further improving the catalytic effect.
[0044] According to the embodiment of the present application, the specific surface area of the second catalyst is 280-350m 2 / g, the molecular sieve includes ZSM-5. Thus, it is beneficial to further improve the catalytic effect.
[0045] The bio-oil produced by the traditional pyrolysis process contains a large number of macromolecular products, and the mass transfer and diffusion in the micropores of molecular sieves such as ZSM-5 and the contact of active centers are limited during the catalytic process, and the catalyst is prone to carbon deposition and deactivation. The second catalyst is modified by the La element to enhance the bio-oil cracking ability, improve the cracking ability of the intermediates, improve the stability of the catalyst, and improve the catalyst's resistance to carbon deposition. In some specific embodiments, the molecular sieve in the second catalyst can be ZSM-5, and the second catalyst is hereinafter referred to as La-ZSM-5.
[0046] In general, the above catalyst composition is used for two-stage catalytic cracking of biomass. In the first stage, the strong cracking and ring-opening effects of Fe-Dol can be used to reduce macromolecular compounds to small molecular intermediates. In the second stage, the intermediates are further catalytically converted by La-ZSM-5 catalyst to generate more light aromatic hydrocarbons: compared with the traditional single catalyst, the two-stage catalyst has a better catalytic effect on pine wood thermal cracking. In the first stage of catalytic cracking, the strong cracking and ring-opening effects of Fe-modified dolomite catalyst can be used to reduce macromolecular compounds to small molecular intermediates. In the second stage of cracking, the intermediates are further catalytically converted by La-modified microporous catalyst ZSM-5 to generate more light aromatic hydrocarbons such as BTX. In addition, the loaded element La makes the ZSM-5 catalyst have a certain anti-coking ability and improves the stability of the catalyst. The catalyst composition alleviates the problem that the mass transfer diffusion and contact of the active center in the ZSM-5 micropores are limited and carbon deposition is easy to occur in the catalytic process of using a single traditional ZSM-5 catalyst due to the large number of macromolecular products in the bio-oil produced during the pyrolysis process.
[0047] In another aspect of the present application, the present application proposes a method for preparing the aforementioned catalyst composition, the method comprising: mixing and stirring an iron-containing raw material with dolomite, and performing a first calcination treatment on the mixed raw material to prepare a first catalyst; preparing an inorganic salt solution of La, and using the inorganic salt solution to impregnate a molecular sieve, and performing a second calcination treatment on the molecular sieve after the impregnation treatment to prepare a second catalyst. The method can easily obtain the aforementioned catalyst composition. The method can easily obtain the aforementioned catalyst composition.
[0048] According to an embodiment of the present application, the iron-containing raw material includes limonite. The dolomite may be pre-ground, screened and subjected to a third calcination treatment to reduce the particle size of the dolomite and enhance the Fe modification effect of the subsequent treatment. The temperature of the third calcination treatment is 850-1000°C and the time is 2-4h. Specifically, the dolomite may be ground and screened to 100 mesh and then calcined at 900-980°C, for example, 950°C for 3h. The preparation of the first catalyst may specifically include:
[0049] The limonite and the treated dolomite are mixed in a mass ratio of 0.5-1, and the mixture is stirred for 30 minutes to be uniformly mixed. The pseudo-boehmite binder and water are added to prepare a slurry, and the granulation treatment is performed. The particle size of the granulation treatment can be (5±1) mm, and the particles are obtained after drying at room temperature for 12 hours. The obtained particles are dried and the first calcination treatment is performed. The temperature of the first calcination treatment is 700-900° C. and the time is 2-4 hours, thereby obtaining the first catalyst.
[0050] According to an embodiment of the present application, the molecular sieve used to prepare the second catalyst may be pre-screened and subjected to a fourth calcination treatment. The temperature of the fourth calcination treatment is 500-600°C and the time is 3-6 hours. Specifically, as mentioned above, the molecular sieve may be HZSM-5 type, screened to form a 100 mesh fine powder. Subsequently, it may be calcined in a muffle furnace at a temperature of 550°C for 4 hours.
[0051] According to a specific example of the present application, the preparation of the second catalyst may include: preparing a La(NO3)3·6H2O solution with a concentration of 0.05-0.13 mol / L, and impregnating the treated molecular sieve. Specifically, 0.08 mol / L La(NO3)3·6H2O can be dissolved in a magnetic stirring solution for 30 minutes. When there are no particles in the solution, the calcined molecular sieve (HZSM-5) is added and stirred for 2 hours under the action of an electromagnetic stirrer. The impregnated molecular sieve is dried and the dried solid is sieved to 100 mesh, a pseudo-boehmite binder and water are added to prepare a slurry, and granulation is performed to obtain particles with a particle size of (5±1) mm, which are dried at room temperature for 12 hours. The dried particles are subjected to the second calcination treatment, and the temperature of the second calcination treatment is 500-600°C and the time is 3-6 hours.
[0052] The above method can obtain a catalyst whose specific surface area, pore size and crystal type are all suitable for catalytic cracking of biomass, and can increase the content of light aromatics in the obtained bio-oil.
[0053] In another aspect of the present application, the present application proposes a method for preparing light aromatic hydrocarbons by cracking biomass using the catalyst composition described above, the method comprising: heating a two-stage tubular furnace to a preset temperature, introducing an inert gas for gas replacement; adding a biomass raw material and a first catalyst to the first-stage tubular furnace, adding a second catalyst to the second-stage tubular furnace, and performing pyrolysis treatment; using a condensing device to collect the bio-oil produced by the pyrolysis treatment, and separating to obtain the light aromatic hydrocarbons.
[0054] This method can effectively improve the content of light aromatics in the obtained bio-oil.
[0055] According to an embodiment of the present application, heating the two-stage tubular furnace to a preset temperature includes: heating the first-stage tubular furnace to 800-900° C., for example, 850° C., at a heating rate of 15-25° C. / min, for example, 20° C. / min. Heating the second-stage tubular furnace to 450-850° C., and the reforming temperature of the pyrolysis reaction is 450-850° C.
[0056] According to an embodiment of the present application, during the pyrolysis treatment, the flow rate of the inert gas introduced is 50-250 mL / min, for example, specifically, it can be 100 mL / min.
[0057] According to an embodiment of the present application, the mass ratio of the first catalyst to the second catalyst is 1:2-2:1.
[0058] For example, in some embodiments, the temperature of the first tube furnace can be raised to about 850°C and the temperature of the second tube furnace can be raised to about 550°C at a rate of 20°C / min. Subsequently, the nitrogen valve can be opened, and nitrogen can be continuously introduced into the system at a certain flow rate, such as 100mL / min, for replacement to maintain an inert atmosphere in the furnace. Subsequently, under the condition of maintaining the flow rate of the inert atmosphere, pine wood particles, Fe / Dol catalyst, and La / ZSM-5 catalyst are respectively wrapped with brass mesh. Pine wood sticks and Fe / Dol catalyst are placed in the first tube furnace, and La / ZSM-5 catalyst is placed in the second tube furnace. Subsequently, the bio-oil can be collected using a condensing device, and then the water in the gas is absorbed by a gas washing bottle filled with color-changing silica gel, and finally the non-condensable gas is collected using a gas collecting bag.
[0059] The bio-oil prepared under the above conditions has a higher content of light aromatics.
[0060] The method proposed in this application is described below by means of specific examples. The methods used in the following examples are conventional methods unless otherwise specified, and the reagents used are commercially available reagents unless otherwise specified.
[0061] The following embodiments adopt the Figure 1 The device shown is carried out. Figure 1 In the figure, each number represents the following equipment: 1. Nitrogen bottle; 2. Rotor flowmeter; 3. Heating device; 4. Crucible; 5. Temperature control system; 6. Condensation system; 7. Drying device; 8. Gas collecting bag.
[0062] The catalyst compositions used in the following examples were prepared by the following method:
[0063] (1) Preparation of La-ZSM-5 catalyst:
[0064] Carrier pretreatment: sieve molecular sieve (HZSM-5) fine powder to 100 mesh, calcine 10-100g molecular sieve powder in a muffle furnace at 550°C for 4h, and take out the molecular sieve after the muffle furnace is cooled to room temperature and sealed for storage;
[0065] Introduction of active components: Using the impregnation method, weigh 3.58 g of (La(NO3)3·6H2O) and add it to 100 ml of deionized water. Place the beaker on a magnetic stirrer and stir for 30 min. When the solution is free of particles, add 20 g of calcined molecular sieves and stir for 2 h under a magnetic stirrer.
[0066] Catalyst molding: Dry the sample at 105°C for 12 hours, sieve to 100 mesh, add 7.86g of pseudo-boehmite and stir evenly, add deionized water and then stretch and granulate to obtain a spherical catalyst with a particle size of (5±1) mm, dry it at room temperature for 12 hours, and after drying, calcine the catalyst particles in a muffle furnace at 550°C for 4 hours. After cooling, seal the catalyst for storage.
[0067] (2) Preparation of Fe / Dol catalyst:
[0068] After natural dolomite is ground and sieved to 100 mesh, 10-100 g of natural dolomite powder is taken and placed in a muffle furnace, calcined at 950° C. for 3 hours, and then sealed and stored after cooling to room temperature to prepare 100 mesh dolomite carrier particles.
[0069] Weigh 7.44g of limonite and 12.56g of dolomite, and mechanically mix and stir for 30 minutes. Then add 6.67g of pseudo-boehmite binder and stir evenly. Add deionized water to the evenly stirred mixture, and perform strand granulation. The particle size is (5±1) mm, and dry at room temperature for 12 hours. Put the dried catalyst into a muffle furnace and calcine at 800℃ for 3 hours. After the heating furnace cools down, put it into a sealed bag for storage.
[0070] Example 1
[0071] Step 1: Turn on the temperature control device of the two-stage tube furnace, and raise the temperature of the first tube furnace on the left to 850°C and the temperature of the second tube furnace on the right to 550°C at a rate of 20°C / min.
[0072] Step 2: After the two-stage tube furnace reaches the target temperature, connect the tube furnace to the condensing device and the drying device. Open the nitrogen valve and continuously introduce nitrogen into the system at a flow rate of 100 mL / min for 30 minutes.
[0073] Step 3: The nitrogen flow rate is maintained at 100 mL / min. 6 g of pine wood particles, 1.5 g of Fe / Dol catalyst, and 1.5 g of La / ZSM-5 catalyst are wrapped with brass mesh respectively. 6 g of pine wood sticks and 1.5 g of Fe / Dol are placed in the first tube furnace, and 1.5 g of La / ZSM-5 catalyst is placed in the second tube furnace.
[0074] Step 4: Use a condensation device to collect the bio-oil, then pass it through a gas washing bottle filled with color-changing silica gel to absorb the moisture in the gas, and finally use a gas collection bag to collect the non-condensable gas.
[0075] Embodiment 2:
[0076] The remaining operations are the same as in Example 1, except that:
[0077] Step 3: The nitrogen flow rate is maintained at 100 mL / min. 6 g of pine wood particles, 2 g of Fe / Dol catalyst, and 1 g of La / ZSM-5 catalyst are wrapped with brass mesh respectively. 6 g of pine wood sticks and 2 g of Fe / Dol are placed in the first section of the tubular furnace, and 1 g of La / ZSM-5 catalyst is placed in the second section of the tubular furnace.
[0078] Embodiment 3:
[0079] The remaining operations are the same as in Example 1, except that:
[0080] Step 3: The nitrogen flow rate is maintained at 100 mL / min. 6 g of pine wood particles, 1 g of Fe / Dol catalyst, and 2 g of La / ZSM-5 catalyst are wrapped with brass mesh respectively. 6 g of pine wood sticks and 1 g of Fe / Dol are placed in the first tube furnace, and 2 g of La / ZSM-5 catalyst is placed in the second tube furnace.
[0081] Embodiment 4:
[0082] The remaining operations are the same as in Example 1, except that:
[0083] Step 1: The temperature of the second tube furnace is raised to 450°C.
[0084] Embodiment 5:
[0085] The remaining operations are the same as in Example 1, except that:
[0086] Step 1: The temperature of the second tube furnace is raised to 650°C.
[0087] Embodiment 6:
[0088] The remaining operations are the same as in Example 1, except that:
[0089] Step 1: The temperature of the second tube furnace is raised to 750°C.
[0090] Embodiment 7:
[0091] The remaining operations are the same as in Example 1, except that:
[0092] Step 1: The temperature of the second tube furnace is raised to 850°C.
[0093] Embodiment 8:
[0094] The remaining operations are the same as in Example 1, except that:
[0095] Step 3: The nitrogen flow rate was maintained at 50 mL / min.
[0096] Embodiment 9:
[0097] The remaining operations are the same as in Example 1, except that:
[0098] Step 3: The nitrogen flow rate was maintained at 150 mL / min.
[0099] Embodiment 10:
[0100] The remaining operations are the same as in Example 1, except that:
[0101] Step 3: The nitrogen flow rate was maintained at 200 mL / min.
[0102] Embodiment 11:
[0103] The remaining operations are the same as in Example 1, except that:
[0104] Step 3: The nitrogen flow rate was maintained at 250 mL / min.
[0105] Comparative Example 1:
[0106] Step 1: Turn on the temperature control device of the two-stage tubular furnace, and raise the temperature of the first-stage tubular furnace on the left to 850°C and the temperature of the second-stage tubular furnace on the right to 850°C at a rate of 20°C / min.
[0107] Step 2: After the two-stage tube furnace reaches the target temperature, connect the tube furnace to the condensing device and the drying device. Open the nitrogen valve and continuously introduce nitrogen into the system at a flow rate of 100 mL / min for 30 minutes.
[0108] Step 3: The nitrogen flow rate was maintained at 100 mL / min. 6 g of pine wood particles and 3 g of Fe / Dol catalyst were wrapped with brass mesh respectively. 6 g of pine wood sticks were placed in the first tube furnace, and 3 g of Fe / Dol catalyst was placed in the second tube furnace.
[0109] Step 4: Use a condensation device to collect the bio-oil, then pass it through a gas washing bottle filled with color-changing silica gel to absorb the moisture in the gas, and finally use a gas collection bag to collect the non-condensable gas.
[0110] Comparative Example 2:
[0111] The difference from Comparative Example 1 is: Step 1, turn on the temperature control device of the two-stage tubular furnace, and raise the temperature of the first-stage tubular furnace on the left to 550°C and the temperature of the second-stage tubular furnace on the right to 550°C at a rate of 20°C / min.
[0112] Step 3: The nitrogen flow rate was maintained at 100 mL / min. 6 g of pine wood particles and 3 g of La / ZSM-5 catalyst were wrapped with brass mesh respectively. 6 g of pine wood sticks were placed in the first tube furnace, and 3 g of La / ZSM-5 catalyst was placed in the second tube furnace.
[0113] The catalysts used in the above examples were characterized by means of XRD, SEM, BET, etc. The physicochemical properties of the catalysts and the loading of the active components of the catalysts were investigated from the aspects of specific surface area, micromorphology and structure, crystal type, active components and content. Table 1 shows the BET characterization results of Fe / Dol and La / ZSM-5 catalysts.
[0114] Table 1
[0115]
[0116]
[0117] Figure 2 The XRD spectra of dolomite before modification (C-Dol) and Fe-modified dolomite catalyst (Fe / Dol) are shown. The diffraction peaks of C-Dol catalyst at 2θ=32.221°, 37.376°, 53.890°, and 64.163° correspond to CaO; the diffraction peaks at 2θ=42.9° and 62.3° correspond to MgO; and the diffraction peak at 2θ=30.911° corresponds to MgSiO. Dolomite can undergo the following reactions at different temperatures:
[0118] T>600℃: CaMg(CO3)2→Ca(CO3)MgO+CO2;
[0119] T>900℃: Ca(CO3)MgO→CaO·MgO+CO2,
[0120] Thus, a CaO·MgO complex is formed, and the performance of dolomite is improved.
[0121] In Fe / Dol, the diffraction peaks at 2θ=24.163°, 33.179°, 35.651°, 40.886°, and 49.493° correspond to Fe2O3; the diffraction peak at 2θ=29.7° corresponds to Fe3O4 (PDF#89-0951). The CaO after decomposition of dolomite interacts with Fe2O3 in limonite to generate Ca2Fe2O5, which corresponds to the diffraction peaks at 2θ=33.408° and 46.586°; the diffraction peak at 2θ=26.624° corresponds to SiO2, which may be that MgSiO3 in C-Dol absorbs heat and decomposes into MgO and SiO2.
[0122] With Figure 2It can be seen that the first catalyst prepared in the present application has the aforementioned characteristic peaks, which can confirm the preparation of the Fe-modified dolomite catalyst.
[0123] Reference Figure 3-5 SEM images at different magnifications ( Figure 3 The magnification is 5000 times. Figure 4 The magnification is 10,000 times. Figure 5 (15000 times magnification) It can be seen that after calcining dolomite at 950℃ (C-Dol), CaMg(CO3)2 in natural dolomite decomposes into CaO·MgO complex and CO2 under high temperature, and the generated CO2 escapes from the surface, so that pores are formed on the surface of dolomite and the structure becomes loose. This phenomenon corresponds to the XRD spectrum. It can be seen from the SEM image of Fe / Dol that after adding limonite, Fe2O3 is distributed on the dolomite carrier in the form of particles, and particle agglomerations are formed on the surface of the dolomite catalyst. The pore structure is richer than that of calcined dolomite, such as Figure 3-Figure 5 (a) in . Figure 3-Figure 5 (b) is the SEM image of untreated dolomite (Dol) at corresponding magnification.
[0124] Depend on Figure 6 It can be seen from the energy spectrum detection results that Ca, Mg, O, and Si elements exist in the dolomite carrier after calcination. After the dolomite is modified with limonite, Fe element appears on the carrier. The Fe element is successfully loaded on the dolomite carrier, and the element is evenly dispersed.
[0125] refer to Figure 7 , referring to the XRD spectrum of the molecular sieve (C-ZSM-5) before modification, the characteristic peaks of the second catalyst (La / ZSM-5) molecular sieve obtained after modification all appear, indicating that the molecular sieve remains stable under different treatment methods and still maintains the MFI structure. After loading the rare earth element La, there is no obvious La element diffraction peak in the XRD crystal phase spectrum, which shows that the La element is evenly dispersed on the molecular sieve, there are no large particle crystals, and therefore no sharp diffraction peaks are formed.
[0126] refer to Figure 8 , 9 At different magnifications ( Figure 8 The magnification is 5000 times. Fig. 9 The SEM electron microscope photos (10000 times magnification, (a) is ZSM-5, (b) is La / ZSM-5) show that after calcination, the surface of ZSM-5 crystals is smooth and flat, while the surface of La-ZSM-5 catalyst becomes rough, some block crystals are broken, and evenly distributed fine debris particles appear on the surface. The overall morphology has no obvious change, indicating that La is highly dispersed on the catalyst surface, which is consistent with the XRD spectrum results. Fig.10 From the energy spectrum detection results, it can be seen that the calcined molecular sieve is composed of three elements: Al, Si, and O. After the molecular sieve is modified with La element, Al, Si, O, and La elements are distributed on the surface, indicating that La element is successfully introduced into the La / ZSM-5 catalyst.
[0127] The products in Example 1 and Comparative Examples 1 and 2 were analyzed using a gas chromatography-mass spectrometer (GC-MS). Fig.11 The results of the relative peak areas of the components in the products of Example 1 and Comparative Examples 1 and 2 are compared. The Fe / Dol and La / ZSM-5 catalyst combination of Example 1 can effectively increase the content of light aromatics and reduce the content of heavy compounds. The relative peak area of light aromatics in the combination reaches a maximum of 40.49%, which exceeds the sum of light aromatics obtained by catalytic pyrolysis of pure Fe / Dol alone (10.96%) and catalytic pyrolysis of pure La / ZSM-5 alone (23.86%).
[0128] Attached Fig.12 The figure shows the variation trend of the light aromatics content in the product when the Fe / Dol and La / ZSM-5 dosages are different in the above embodiment. Fig.12 It can be seen that the light aromatic content in the above embodiments generally increases first and then decreases, indicating that La / ZSM-5 is beneficial to the conversion of other substances into light aromatics. As the mass proportion of La / ZSM-5 increases, it helps the deoxygenation and cracking of pyrolysis gas, and more pyrolysis gas is converted into light aromatics. However, as the mass proportion of Fe / Dol becomes smaller and smaller, the initial catalytic cracking of the primary volatile matter of biomass is incomplete. When the mass ratio of the two is 1.5:1.5, the catalytic effect reaches a dynamic balance. At this time, more heterocyclic polycyclic aromatic hydrocarbons and heavy polycyclic aromatic hydrocarbons are converted into light aromatic hydrocarbons, the bio-oil has a low oxygen content, and the light aromatic hydrocarbon content is the highest.
[0129] Attached Fig.13 The figure shows the variation trend of the light aromatics content in the product when the reforming temperature of the pyrolysis treatment in the above embodiment is different. Fig.13 It can be seen that when the reforming temperature increases from 450°C to 550°C, the selectivity of light aromatics increases from 24.34% to 40.49%. When the temperature is greater than 550°C, the selectivity of light aromatics decreases rapidly to 11.58%. Therefore, 550°C is the optimal reforming temperature for preparing light aromatics. It is worth noting that the change trend of light polycyclic aromatic hydrocarbons is opposite to that of light aromatic hydrocarbons. At higher temperatures, light aromatic hydrocarbons may react with other oxygen-containing compounds on the surface of La / ZSM-5 catalyst and be converted into polycyclic aromatic hydrocarbons.
[0130] Attached Fig.14 The figure shows the variation trend of the light aromatics content in the product when the inert gas flow rate is different in the above embodiment. Fig.14It can be seen that when the gas flow rate is 50mL / min, the time of the biomass pyrolysis gas and the two-stage catalytic reaction of Fe / Dol and La / ZSM-5 is too long, and the light hydrocarbons generated react with oxygen-containing substances to form heterocyclic compounds, resulting in a decrease in the quality of bio-oil. When the gas flow rate is 100mL / min, the aromatics generated by the two-stage catalytic reaction of biomass pyrolysis gas and Fe / Dol and La / ZSM-5 are directly carried out of the reactor by the inert gas, so the content of light aromatics reaches the highest. When the flow rate is greater than 100mL / min, the reaction time of biomass pyrolysis gas and the two-stage catalyst is short, and some heterocyclic aromatics or polycyclic aromatics have not been catalyzed by Fe / Dol and La / ZSM-5. Therefore, too high a gas flow rate is not conducive to the production of light aromatics and the improvement of bio-oil quality.
[0131] The results of the example show that when Fe / Dol and La / ZSM-5 are combined for catalysis, the yield of liquid products increases, which is higher than the sum of the relative contents of light aromatics obtained by Fe / Dol and La / ZSM-5 alone, and the quality of bio-oil is improved, with the BTX content reaching a maximum of 40.49%, the oxygen content dropping to a minimum of 22.96%, and the polycyclic compounds dropping to 0.72%. Characterization of the reused catalysts revealed that when Fe / Dol and La / ZSM-5 were used five times, slight sintering and agglomeration occurred, but the Fe and La elements were evenly distributed on the carrier, and the yield of the three-phase product remained basically stable. The Fe / Dol and La / ZSM-5 catalysts still had high catalytic activity and stability.
[0132] The above application provides many different embodiments or examples to realize the different structures of the present application. In order to simplify the present application, the parts and settings of specific examples are described above. Of course, they are only examples, and the purpose is not to limit the present application. In addition, the present application can repeat reference numbers and / or reference letters in different examples, and this repetition is for the purpose of simplification and clarity, which itself does not indicate the relationship between the various embodiments and / or settings discussed.
[0133] The above are only specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any technician familiar with the technical field can easily think of various changes or substitutions within the technical scope disclosed in the present application, which should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A catalyst composition for preparing light aromatic hydrocarbons by cracking biomass, characterized in that: The catalyst composition comprises a first catalyst and a second catalyst, wherein the first catalyst comprises Fe-modified dolomite particles, and the second catalyst comprises La-modified molecular sieve. The Fe-modified dolomite particles are formed by mechanically mixing and sintering the iron-containing raw material and the dolomite, and the Fe content in the Fe-modified dolomite particles is 4-8wt%; The La-modified molecular sieve is formed by sintering a molecular sieve impregnated with lanthanum nitrate, and the La content in the La-modified molecular sieve is 3-8wt%.
2. The catalyst composition according to claim 1, characterized in that The specific surface area of the first catalyst is 15-30m 2 / g, and the evaluation pore size of the first catalyst is 20-30nm.
3. The catalyst composition according to claim 1, characterized in that The specific surface area of the second catalyst is 280-350m 2 / g, and the molecular sieve includes ZSM-5.
4. A method for preparing the catalyst composition according to any one of claims 1 to 3, characterized in that: include: The iron-containing raw material and dolomite are mixed and stirred, and the mixed raw material is subjected to a first calcination treatment to prepare a first catalyst; An inorganic salt solution of La is prepared, and the molecular sieve is impregnated with the inorganic salt solution. The molecular sieve impregnated with the inorganic salt solution is subjected to a second calcination treatment to prepare a second catalyst.
5. The method according to claim 4, characterized in that The iron-containing raw material includes limonite, the dolomite is pre-ground, screened and subjected to a third calcination treatment, the temperature of the third calcination treatment is 850-1000° C., and the time is 2-4 hours. The preparation of the first catalyst includes: The limonite and the dolomite subjected to the third calcination treatment are mixed in a mass ratio of 0.5-1 and stirred evenly, pseudo-boehmite binder and water are added to prepare slurry, and granulation treatment is performed, the particles obtained by the granulation treatment are dried, and the first calcination treatment is performed, and the temperature of the first calcination treatment is 700-900°C and the time is 2-4h.
6. The method according to claim 4, characterized in that The molecular sieve is pre-screened and subjected to a fourth calcination treatment, wherein the temperature of the fourth calcination treatment is 500-600° C. and the time is 3-6 hours. The preparation of the second catalyst comprises: A La(NO3)3·6H2O solution with a concentration of 0.05mol / L-0.13mol / L is prepared, and the treated molecular sieve is impregnated, wherein the impregnation treatment includes impregnation for 1.5-3h under stirring conditions, the molecular sieve that has undergone the impregnation treatment is dried and the dried solid is sieved to 100 mesh, a pseudo-boehmite binder and water are added to prepare a slurry, and granulation treatment is performed, the particles obtained by the granulation treatment are dried, and the second calcination treatment is performed, wherein the temperature of the second calcination treatment is 500-600°C and the time is 3-6h.
7. A method for preparing light aromatic hydrocarbons by cracking biomass using the catalyst composition according to any one of claims 1 to 3, characterized in that: include: After the two-stage tube furnace is heated to the preset temperature, an inert gas is introduced for gas replacement; Adding biomass raw materials and a first catalyst into the first-stage tubular furnace, and adding a second catalyst into the second-stage tubular furnace to perform pyrolysis treatment; The bio-oil produced by the pyrolysis treatment is collected by a condensing device, and the light aromatics are obtained by separation.
8. The method according to claim 7, characterized in that Heating a two-stage tube furnace to a preset temperature involves: The temperature of the first tube furnace is raised to 800-900°C at a heating rate of 15-25°C / min, and the temperature of the second tube furnace is raised to 450-850°C. The reforming treatment temperature of the pyrolysis treatment is 450-850°C.
9. The method according to claim 8, characterized in that During the pyrolysis treatment, the flow rate of the inert gas introduced is 50-250 mL / min.
10. The method according to claim 9, characterized in that The mass ratio of the first catalyst to the second catalyst is 1:2-2:1.